2008
DOI: 10.1021/ja807284e
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynaphthyridine-Derived Group III Metal Chelates: Wide Band Gap and Deep Blue Analogues of Green Alq3 (Tris(8-hydroxyquinolate)aluminum) and Their Versatile Applications for Organic Light-Emitting Diodes

Abstract: A series of group III metal chelates have been synthesized and characterized for the versatile application of organic light-emitting diodes (OLEDs). These metal chelates are based on 4-hydroxy-1,5-naphthyridine derivates as chelating ligands, and they are the blue version analogues of well-known green fluorophore Alq(3) (tris(8-hydroxyquinolinato)aluminum). These chelating ligands and their metal chelates were easily prepared with an improved synthetic method, and they were facially purified by a sublimation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(63 citation statements)
references
References 94 publications
0
62
0
Order By: Relevance
“…We have also explained that the basis set has no significant effect on absorption wavelength and the absorption and emission energies have been calculated by TDDFT at the PBE0/6-31G(D) level using B3LYP/6-31G(D) and CIS/6-31G(D) optimized geometries respectively. Here also similar to the previous study the absorption and emission wavelengthsof (1)(2)(3)(4)(5)(6)(7)(8) have been computed at the same level of theory and are summarized in Table 6, along with the experimentally reported absorption and emission wavelengths of merAlND3 [52] The ligand atom labels used in the text for the disubstituted AlND3 complexes considered in this study in Table 4 and Table S2(a-d) (for EDG and EWG labels are not shown). The NBO charges (Q) of the ligands in 1 and 5, in the optimized ground (Q HF-S0 ) and first excited (Q S1 ) states structures and the charge differences between Q HF-S0 and Q S1 states calculated at the HF/6-31G(D) and CIS/6-31G(D) methods, respectively (for atom labels see Fig.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 62%
See 4 more Smart Citations
“…We have also explained that the basis set has no significant effect on absorption wavelength and the absorption and emission energies have been calculated by TDDFT at the PBE0/6-31G(D) level using B3LYP/6-31G(D) and CIS/6-31G(D) optimized geometries respectively. Here also similar to the previous study the absorption and emission wavelengthsof (1)(2)(3)(4)(5)(6)(7)(8) have been computed at the same level of theory and are summarized in Table 6, along with the experimentally reported absorption and emission wavelengths of merAlND3 [52] The ligand atom labels used in the text for the disubstituted AlND3 complexes considered in this study in Table 4 and Table S2(a-d) (for EDG and EWG labels are not shown). The NBO charges (Q) of the ligands in 1 and 5, in the optimized ground (Q HF-S0 ) and first excited (Q S1 ) states structures and the charge differences between Q HF-S0 and Q S1 states calculated at the HF/6-31G(D) and CIS/6-31G(D) methods, respectively (for atom labels see Fig.…”
Section: Absorption and Emission Propertiesmentioning
confidence: 62%
“…The geometry of these derivatives is constructed by using the reported x-ray coordinates of the parent mer-AlND3 [52], which possesses C 1 -symmetry. The geometry optimizations have been carried out using DFT/B3LYP/6-31G(D) method using G09 package [53].…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations